Pattern of Morphological Variability in Unrepaired Unilateral Clefts With and Without Cleft Palate May Suggest Intrinsic Growth Deficiency - Latief, Benny S.; Kuijpers, Mette A. R.; Stebel, Adam; Kuijpers-Jagtman, Anne Marie; Fudalej, Piotr S. (Frontiers in Cell and Developmental Biology, 2020)
In individuals with cleft lip and palate (CLP) an iatrogenic effect of operations on subsequent maxillary growth is well-known. Much less is known about the association between occurrence of CLP and intrinsic growth deficiency of the maxillofacial complex. The aim of this study was to compare morphological variability in subjects with unilateral cleft lip and alveolus/palate and unaffected controls using geometric morphometric methods. The research hypothesis was that if subjects with unrepaired unilateral CLP have intrinsic growth deficiency, the pattern of their craniofacial growth variation may differ from that in unaffected individuals. Lateral cephalograms were available of three groups of the same ethnic background (Proto-Malayid): (a) non-syndromic unrepaired unilateral complete cleft lip, alveolus, and palate (UCLP), N = 66, mean age 24.5 years (b) non-syndromic unrepaired unilateral complete cleft lip and alveolus (UCLA), N = 177, mean age 23.7 years, and (c) NORM (N = 50), mean age 21.2 years without a cleft. Using geometric morphometrics shape variability in groups and shape differences between groups was analyzed. Principal component analysis (PCA) was used to examine shape variability, while differences between groups and sexes were evaluated with canonical variate analysis. Sexual dimorphism was evaluated with discriminant function analysis (DA). Results showed that in comparison to NORM subjects, shape variability in UCLA and UCLP is more pronounced in the antero-posterior than in vertical direction. Pairwise comparisons of the mean shape configurations (NORM vs. UCLA, NORM vs. UCLP, and UCLA vs. UCLP) revealed significant differences between cleft and non-cleft subjects. The first canonical variate (CV1, 68.2% of variance) demonstrated that differences were associated with maxillary shape and/or position and incisor inclination, while in females, the CV1 (69.2% of variance) showed a combination of differences of “maxillary shape and/or position and incisor inclination” and inclination of the cranial base. Shape variability demonstrated considerable differences in subjects with UCLA, UCLP, and NORM. Moreover, in subjects with a cleft, within-sample variability was more pronounced in the antero-posterior direction, while in non-cleft subjects, within-sample variability was more pronounced in the vertical direction. These findings may suggest that subjects with unilateral clefts have intrinsic growth impairment affecting subsequent facial development.